Optimization And Business Risk Analysis On Independent Oil Palm Farming In Muara Tembesi District, Batanghari Regency - Alamsyah, Zulkilfi; Suandi; Damayanti, Yusma; Oktari Ulma, Riri; Effran, Endy (Journal of Agri Socio Economics and Business, 2023)
This study aims to analyze the optimal use of production factors and business risks in independent palm oil farming. This research was conducted in Jebak, Ampelu, and Ampetu Mudo, Muara Tembesi District villages. The analytical method used is descriptive and quantitative analysis. Descriptive method to see the description of farming. A quantitative method to analyze input usage by using the cobb-Douglas function. The sample villages were determined purposively based on the consideration that the three villages had the largest area of productive plantations (TM). Determination of the number of samples used the census method with a total of 116 respondents. The results showed that (1) palm oil production produced from oil palm farming activities in the study area averaged 15,025.18 kg/ha/year with an average selling price of Rp. 2.208/kg. Farmers operate oil palm farming with a land area of 2.55 ha/farmer, plant age of 10.87 years, fertilizer 243.92 kg/ha/year, herbicides 2.29 liters/ha/year, and labor 88.60 HOK /ha/year. (2). Partially, the variables of land area, plant age, and use of fertilizers have a positive and significant effect on independent oil palm production in Muara Tembesi District, Batanghari Regency, while the variables use of herbicides and use of labor do not have a significant effect on oil palm production. The optimal use of production factors for a land area of 3.82 ha and fertilizer use is 1,053.55 kg/ha/year. (3). Independent oil palm farming is consistently profitable, with a CV value <0.5, the L value > 0, and the R/C value obtained is R/C = 4.45 per farmer and R/C = 4.48 per hectare.